2002
DOI: 10.1097/00004694-200203000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to evaluate the effect of forearm position on residual fracture angulation for pediatric distal-third forearm fractures at the time of union. One hundred nine pediatric distal-third forearm fractures undergoing closed reduction and casting were prospectively randomized to be immobilized in pronated, supinated, or neutral position. Initial angulation and displacements were radiographically compared with healed fracture angulation at a minimum of 6 weeks. With 99 complete patient fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…(2002) suggested that all displaced fractures with an angulation of more than 15° require closed reduction 14. In this series, all children with angulation of more than 20° were advised closed reduction and cast molding.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…(2002) suggested that all displaced fractures with an angulation of more than 15° require closed reduction 14. In this series, all children with angulation of more than 20° were advised closed reduction and cast molding.…”
Section: Discussionmentioning
confidence: 89%
“…ROC estimation suggested that the cutoff point for CI should be 0.84 (when there is high sensitivity as well as specificity) for identifying children who require re-manipulation. All the previous reports have shown that the treatment failure group has a mean CI of 0.80 56142225…”
Section: Discussionmentioning
confidence: 92%
“…The same has been shown for positioning the wrist in pronation/neutral/supination. 12 13 Despite this, uniform cast molding and positioning techniques were used throughout this study.…”
Section: Discussionmentioning
confidence: 99%
“…Forearm fractures are among the most common lesions in pediatric patients [ 1 , 2 ]. 20-30% of the cases involve distal metaphysis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%